El aula rural: un espacio para aprender juntos - Ligia María Angulo-Hernández; Yadira Cerdas-Rivera; Sandra Ovares-Barquero (Revista Electrónica Educare)
This article summarizes the most significant results of research carried out with two female teachers and a male teacher who work is school whit only one instructor located in the Pacific, Atlantic and Central areas of the country.